2019
DOI: 10.1200/jco.2019.37.15_suppl.8013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical responses and pharmacokinetics of fully human BCMA targeting CAR T-cell therapy in relapsed/refractory multiple myeloma.

Abstract: 8013 Background: Previous studies indicate patients with relapsed/refractory multiple myeloma (RRMM) who receive high-dose BCMA-targeting CAR-T cells may achieve better remission but have worse adverse events. Moreover, once the disease progresses again, the re-infusion of CAR-T cells is not effective. To solve this dilemma, we have developed a novel BCMA-targeting CAR-T (CT103A) with a lentiviral vector containing a CAR structure with a fully human scFv, CD8a hinger and transmembrane, 4-1BB co-stimulatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Out of these, 47 studies were excluded: 20 were still recruiting and without outcome data or were not restricted to CAR T‐cell therapy, 21 reported outcomes only on a single case basis, and 6 studies evaluated safety and efficacy of CAR T cells targeting antigens other than BCMA. Of the remaining 18 studies, 3 were included only in the qualitative review because they evaluated CAR T products that, in addition to BCMA, targeted other antigens such as CD19 and CD38 . The remaining 15 studies were included in the quantitative systematic review and meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these, 47 studies were excluded: 20 were still recruiting and without outcome data or were not restricted to CAR T‐cell therapy, 21 reported outcomes only on a single case basis, and 6 studies evaluated safety and efficacy of CAR T cells targeting antigens other than BCMA. Of the remaining 18 studies, 3 were included only in the qualitative review because they evaluated CAR T products that, in addition to BCMA, targeted other antigens such as CD19 and CD38 . The remaining 15 studies were included in the quantitative systematic review and meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
“…shows the PRISMA flow diagram of the study selection process. Out of 18 identified studies, three were included only in the qualitative review because they evaluated CAR T products that, in addition to BCMA, targeted other antigens such as CD19 and CD38 . The remaining 15 studies were included in the quantitative systematic review and meta‐analysis…”
Section: Resultsmentioning
confidence: 99%
“…No NTX was observed. One patient died of lung infection at day 19 post-infusion [111,138]. Despite this encouraging preliminary result, further studies are still warranted to evaluate the safety and efficacy of this fully human BCMA-targeted CT103A.…”
Section: Ct103amentioning
confidence: 96%
“…Currently, there are many ongoing CAR-T studies for BCMA, such as JCARH125 [ 103 ], CT053 [ 104 ], MCARH171 [ 105 ], and CT103A [ 106 ]. These studies also showed a good response rate, and no new treatment toxicity and side effect was observed.…”
Section: Chimeric Antigen Receptor (Car)-t Cellsmentioning
confidence: 99%